PENERAPAN ARTIFICIAL INTELLIGENCE UNTUK OPTIMALISASI KINERJA KARANG TARUNA - Ariani, Fattya; Sumarna; Nurdin, Hafis; Supriyadi, Riki (LPPM Universitas Insan Pembangunan, 2024)
Karang Taruna RW 06 in Tegal Parang Village faces challenges in carrying out community activities, including organizing events, managing data, and making strategic decisions. Some of the problems faced include limited human resources, limited access to modern technology, and minimal understanding of the benefits and potential of artificial intelligence (AI). To overcome this problem, it is necessary to apply effective AI to increase members' creativity in creating information about promotional activities, such as creating and distributing flyers and brochures. In addition, AI can strengthen internal and external communications and facilitate better collaboration between Karang Taruna members and the community. In this effort, lecturers at Nusa Mandiri University, Faculty of Technology and Information, held training on the application of AI to optimize the performance of Karang Taruna RW 06. This training inspired other Karang Taruna to utilize AI to improve performance and provide a wider positive impact on society. , including making digital brochures and flyers for promotional activities as well as making press releases that will be published electronically.